Combined Effects of Midlevel Dry Air and Vertical Wind Shear on Tropical Cyclone Development. Part I: Downdraft Ventilation - Alland, Joshua J.; Tang, Brian H.; Corbosiero, Kristen L.; Bryan, George H. (Journal of the atmospheric sciences, 2021)
This study examines how midlevel dry air and vertical wind shear (VWS) can modulate tropical cyclone (TC) development via downdraft ventilation. A suite of experiments was conducted with different combinations of initial midlevel moisture and VWS. A strong, positive, linear relationship exists between the low-level vertical mass flux in the inner core and TC intensity. The linear increase in vertical mass flux with intensity is not due to an increased strength of upward motions but, instead, is due to an increased areal extent of strong upward motions ( w > 0.5 m s −1 ). This relationship suggests physical processes that could influence the vertical mass flux, such as downdraft ventilation, influence the intensity of a TC. The azimuthal asymmetry and strength of downdraft ventilation is associated with the vertical tilt of the vortex: downdraft ventilation is located cyclonically downstream from the vertical tilt direction and its strength is associated with the magnitude of the vertical tilt. Importantly, equivalent potential temperature of parcels associated with downdraft ventilation trajectories quickly recovers via surface fluxes in the subcloud layer, but the areal extent of strong upward motions is reduced. Altogether, the modulating effects of downdraft ventilation on TC development are the downward transport of low–equivalent potential temperature, negative-buoyancy air left of shear and into the upshear semicircle, as well as low-level radial outflow upshear, which aid in reducing the areal extent of strong upward motions, thereby reducing the vertical mass flux in the inner core, and stunting TC development.